The Independent Curriculum Approach in Supporting Implementing Cultural Values in Students' Character Education in The Era of Globalization - Prawita, Citra Bella; Firman, Firman; Harun, Maizatul Mardiana (Widyagogik, 2024)
Education plays a crucial role in shaping the character and personality of the younger generation. In the current era of globalization, which is characterized by rapid changes and widespread external influences, the role of teachers in character education, especially in the application of cultural values, has become even more vital. Teachers are not only responsible for teaching academic subjects, but also for guiding students in understanding, appreciating, and applying cultural values in their daily lives. The increasing challenges of globalization, such as the erosion of local cultures and values, make it even more critical for educators to play an active role in nurturing a strong sense of identity and cultural awareness in students. This research aims to explore and describe the various efforts made by teachers to instill cultural values through character education in students, particularly in the context of globalization. The study seeks to identify the methods and strategies teachers use to effectively incorporate cultural values into their teaching practices. The research utilizes a descriptive qualitative approach, employing data analysis techniques based on the Miles and Huberman model. The subjects of this research are teachers from SD Negeri 18 Air Tawar Selatan, who are directly involved in the process of character education. The results of this research reveal that teachers at SD Negeri 18 Air Tawar Selatan make significant efforts to instill cultural values in their students. One of the key strategies used is the decoration of classrooms, which serves as a visual reminder of cultural heritage and values. Additionally, teachers integrate cultural values into the curriculum, ensuring that lessons are not only academically enriching but also culturally relevant. Through these efforts, teachers create an environment that fosters cultural awareness and encourages students to take pride in their cultural identity. The research highlights the importance of these practices in shaping the future of students, ensuring that they grow up to be individuals who respect and uphold the cultural values of their society, even in the face of globalization.